(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Caligula never set foot on Hispanic soil and his only relationship was to gradually close all those monetary workshops so that Rome and Lugdunum would be the only mints that would economically feed the needs of his subjects. It is possible that the abundance of coins minted during the governments of Augustus and Tiberius partially alleviated the need for coins at the mints that still functioned during their government. From 39 A.D. onwards, he granted the administration of the coinage and public revenues to slaves of his house to the detriment of the Senate, which he humiliated, earning his eternal hatred for his social and political investment. As García y Bellido (2006:649) points out, for the first time since Augustus in Hispania more coinage minted in Rome circulated than that issued in Hispania itself, taking into account that after the death of Caligula and the monetary damnatio ordered by Claudius, the percentage of coinage in circulation would be greatly reduced. The percentage of coins found in excavations in Roman camps in the northwest of Hispania is particularly insignificant, about 7 coins out of more than 1,130 found.